Penerapan Sapta Pesona Dalam Meningkatkan Kunjungan Wisata Di Pantai Cemara Indah Desa Gosong Telaga Kecamatan Singkil Utara Kabupaten Aceh Singkil - Rasbina Christian Manik (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
The tourism industry is a very important part of the development of society in this modern era. Aceh Singkil Regency with its natural potential offers destinations such as Cemara Indah Beach. Even though it suffered damage due to abrasion, the government and society are trying to restore it. It is necessary to implement Sapta Pesona to increase tourist visits. This research aims to evaluate the application of Sapta Pesona at Cemara Indah Beach, providing theoretical and practical benefits as a reference with the hope of developing tourist attractions and community participation in the tourism industry. The research method used by researchers is qualitative research with a descriptive approach through in-depth interview techniques with informants. This research was carried out by collecting data from informants, namely tourism managers, tourists, business actors and village governments. This research shows that the integration of the Sapta Pesona concept into the Cemara Indah Beach tourist attraction has had a significant positive impact. Security and other elements of Sapta Pesona are effective in increasing the attractiveness of the destination. Further development recommendations are needed to ensure sustainable growth, attract more visitors and have a positive impact on the local economy. In conclusion, the implementation of Sapta Pesona at Cemara Indah Beach shows the management's commitment to improving the quality of the destination. Although efforts have been made to create a safe and clean environment, several obstacles such as local community involvement, changes in tourist behavior, infrastructure, and economic factors still need to be overcome. Suggestions involve educational campaigns, community participation, infrastructure improvements, collaboration with the private sector, sustainable economic initiatives, security technology, and improving service quality. With these steps, Cemara Indah Beach has the potential to become an attractive and sustainable tourist destination.